Design of Reference Model Adaptive Based Discrete-Time PID Controller for Satellite Yaw-Axis Attitude Control System - Emmanuel E. Egwim; Ikemsinachi Chikeziri Osuagwu; Nnanyereugo Nnamdi Emeribe (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Effective satellite attitude control systems are essential to ensure both the quality and reliability of data acquisition in microsatellites. This paper presents the design and performance analysis of an adaptive controller for a microsatellite yaw-axis (y-axis) attitude control system (ACS). The transfer function models of the amplifier, actuator, and satellite structure were first derived to obtain the overall transfer function of the microsatellite yaw-axis attitude dynamics. Based on these models, a Model Reference Adaptive Control–based Discrete-Time Proportional–Integral–Derivative controller (MRAC-DPID) was designed and integrated into the closed-loop network of the microsatellite yaw-axis ACS. A computer-based MATLAB/Simulink model was then developed using the mathematical representation of the closed-loop system, and simulations were conducted to evaluate the attitude response under the MRAC-DPID controller. The simulation results demonstrate that the proposed MRAC-DPID significantly improves both transient and steady-state performance, as reflected in reduced rise time, settling time, overshoot, and steady-state error. Overall, the controller satisfies all specified performance criteria and provides the best step-response performance with respect to overshoot for adaptation gains in the range of 0.1 to 1. The study concludes that the MRAC-DPID controller offers an effective adaptive control strategy for microsatellite yaw-axis attitude regulation, thereby supporting improved stability and reliability of microsatellite operations.